Oxidative stress and antioxidant vitamins in leprosy - Trimbake, Sangeeta B.; Sontakke, Alka N.; Dhat, Vaishali V. (International Journal of Research in Medical Sciences, 2017)
Background: Leprosy is a disease of great antiquity and it still continues to be a significant public health problem in few countries including India .Of the various mechanisms that influence the pathogenesis of leprosy, oxidative stress is important which occurs due to derangement in the balance between ROS and natural antioxidants. Hence this study attempted to assess the oxidative stress and antioxidant status in terms of MDA and vitamin E, vitamin C respectively in leprosy. Methods: Hundred untreated leprosy patients (50 PB and 50 MB) were studied and compared with 50 healthy controls. Serum Malondialdehyde (MDA) and vitamin E, vitamin C was measured by spectrophotometric method. Serum malondialdehyde (MDA) was measured as an indicator of lipid peroxidation and antioxidant status was assessed by estimating serum vitamin E and vitamin C levels. Results: Significant rise in serum MDA (P <0.001) in both PB and MB leprosy was seen when compared with controls. The vitamin E level was significantly decreased in both PB and MB leprosy patients as compared to controls. The vitamin C level was significantly decrease (P<0.001) in MB leprosy patients as compared to controls. Conclusions: Elevated MDA levels indicate oxidative stress in leprosy patients, denoting its crucial involvement in the pathogenesis and tissue damage in leprosy. Hence MDA levels can be used to monitor prognosis, treatment and control of leprosy. Decreased vitamin E, C levels in leprosy can be improved by oral vitamin E, C supplementation.